The influence of polymethyl acrylate as a pour point depressant for biodiesel. Issue 1 (2nd January 2017) - Xue, Yuan; Yang, Chao; Xu, Guangwen; Zhao, Zhicheng; Lian, Xiang; Sheng, Han; Lin, Hualin
ABSTRACT: Waste cooking oil biodiesel (BWCO) was used to investigate the influences of polymethyl acrylate (PMA) pour point depressant mixed with common dispersants on the cold flow property of biodiesel. Results showed that PMA mixed with Span80 dispersant at a mass ratio of 2:1 exhibited the best synergistic effect on reducing the cold filter plugging point (CFPP) by 7°C with respect to pure biodiesel. Performance mechanisms were also explored and showed that mixed improvers have better dissolution and dispersion in biodiesel, effectively inhibited the formation of larger crystals, and reduced the amount and sizes of crystals, thereby improving the cold flow properties of biodiesel.